The Panoplia dogmatike by Euthymios Zygadenos : a study on the first edition published in Greek in 1710 - Miladinova, Nadia. (Texts and Studies in Eastern Christianity, 2014)
Created in the twelfth century, the Panoplia Dogmatike is one of the Byzantine anthologies that became a key source for Orthodox theology. The anthology is known in more than 140 Greek manuscripts. In the fourteenth century it was translated into Old Church Slavonic. The Latin translation, prepared by the Italian humanist Pietro Francesco Zini, was published in Venice in 1555 during the years of the Council of Trent. The first printed edition of the Greek text came relatively late - in 1710 in the Romanian Principality of Wallachia. By examining the reasons for this publication, the book gives snapshots of the history of this authoritative anthology in the early modern period and uses sources until now not related to the Panoplia.